2004
DOI: 10.1088/1367-2630/6/1/037
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous scaling and universality in hydrodynamic systems with power-law forcing

Abstract: The problem of the interplay between normal and anomalous scaling in turbulent systems stirred by a random forcing with a power law spectrum is addressed. We consider both linear and nonlinear systems. As for the linear case, we study passive scalars advected by a 2d velocity field in the inverse cascade regime. For the nonlinear case, we review a recent investigation of 3d Navier-Stokes turbulence, and we present new quantitative results for shell models of turbulence. We show that to get firm statements is n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
4
23
0
Order By: Relevance
“…Nevertheless, this randomly forced model has played an important role historically. Thus it has been studied numerically via the pseudo-spectral method [119,120]. These studies have shown that, even though the stochastic forcing destroys the vorticity tubes that we have described above, it yields multiscaling of velocity structure that is consistent, for y = 4, with the analogous multiscaling in the conventional 3D Navier-Stokes equation, barring logarithmic corrections.…”
Section: D Navier-stokes Turbulencementioning
confidence: 94%
“…Nevertheless, this randomly forced model has played an important role historically. Thus it has been studied numerically via the pseudo-spectral method [119,120]. These studies have shown that, even though the stochastic forcing destroys the vorticity tubes that we have described above, it yields multiscaling of velocity structure that is consistent, for y = 4, with the analogous multiscaling in the conventional 3D Navier-Stokes equation, barring logarithmic corrections.…”
Section: D Navier-stokes Turbulencementioning
confidence: 94%
“…For 0 < ε < 2, these results are also consistent with the direct numerical simulations of Refs. [19,20].…”
Section: A Simplified Modelmentioning
confidence: 99%
“…It is therefore difficult to decide whether or not the saturation occurs. As discussed in [44], one can understand the curvature of the local slopes with the presence of sub-dominant terms, e.g., with the superposition of two power laws P 2 (r) ≃ Ar a + Br b . In our case, one can expect that…”
Section: A Saturation Of the Correlation Dimensionmentioning
confidence: 99%